Neural Network Technology of the Financial and Economic Model Synthesis of Production as the Fragment of the Economy Digitalization - Alyoshin, Sergei; Borodina, Elena; Hafiiak, Alla; Nosach, Oleksandr (International Journal of Engineering and Technology, 2018)
The purpose of the article is to develop a technology for desgning neural network models for automatic monitoring of the tax burden to achieve the optimal balance between the possibility of developing a successful business and sufficient filling of the regional budget. A multi-layer perceptron and a back-propagation algorithm were applied for the research as well as a neural control technology. The automation of the process of determining the elements of the gradient vector was produced in implementing traditional method of the back-propagation of error by using neural control technology. For the first time, a solution to optimize the fiscally-tax burden (FTB) of the region has proposed with the application of the back-propagation algorithm. Using the proposed methodology a software tool will be created for the transition to an automatic system for optimal management of the economy.Â Â Â